2020
DOI: 10.1002/ecs2.3141
|View full text |Cite
|
Sign up to set email alerts
|

Western bumble bee: declines in the continental United States and range‐wide information gaps

Abstract: In recent decades, many bumble bee species have declined due to changes in habitat, climate, and pressures from pathogens, pesticides, and introduced species. The western bumble bee (Bombus occidentalis), once common throughout western North America, is a species of concern and will be considered for listing by the U.S. Fish and Wildlife Service (USFWS) under the Endangered Species Act (ESA). We attempt to improve alignment of data collection and research with USFWS needs to consider redundancy, resiliency, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
55
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 28 publications
6
55
2
Order By: Relevance
“…1c; Unpublished analysis from Richardson 2019;The Xerces Society et al 2019). These data are corroborated by a recent occupancy modeling analysis, which found that the probability of occupancy by the western bumble bee has declined by 93% over the last 21 years (Graves et al 2020). The western bumble bee is an SGCN in California (CDFW 2015).…”
supporting
confidence: 69%
“…1c; Unpublished analysis from Richardson 2019;The Xerces Society et al 2019). These data are corroborated by a recent occupancy modeling analysis, which found that the probability of occupancy by the western bumble bee has declined by 93% over the last 21 years (Graves et al 2020). The western bumble bee is an SGCN in California (CDFW 2015).…”
supporting
confidence: 69%
“…nevadensis (Cole et al, 2020; Thorp et al, 1983) and B . morrisoni have previously been collected (CDFW, 2019; Graves et al, 2020; Thorp et al, 1983; Table 2). Similarly, the current range of B .…”
Section: Discussionmentioning
confidence: 99%
“…Bombus occidentalis was historically widespread across the state (Thorp et al, 1983), but is now restricted to high meadows (CDFW, 2019;Graves et al, 2020). This species appears to still be sporadically present in the Sierra Nevada (Cole et al, 2020;Hatfield & LeBuhn, 2007), and the Northern Coast Range (Graves et al, 2020), although we did not sample it in either of these ecoregions, which is consistent with another recent study in the Sierra Nevada (Loffland et al, 2017). The documented decline of B. occidentalis began in the mid-1990s in the most western parts of its range, including in California (Cameron, Jepsen, et al, 2011;Graves et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Occupancy models use detection-nondetection data collected across multiple surveys of selected sampling units to estimate the probability that a species occupies, or uses, a unit while accounting for imperfect detection (i.e., false absences). While broadly applied in vertebrate systems, occupancy models have only recently been used in studies of bees (Graves et al, 2020;Landsman et al, 2019;McCune et al, 2020). These studies suggest bee detection probability is not perfect and varies with weather, time of year, and sampling effort, thereby highlighting the need to account for imperfect detection.…”
Section: Single-season Single-species Occupancy Modelsmentioning
confidence: 99%